Influencia de la modernización de la infraestructura en la competitividad del Puerto Salaverry-Trujillo período 2018 - 2019 - Carbajal Zavaleta, Mirella Ghamelit (2021)
The tarjet of this research is to determine the influence of the modernization of its infrastructure, in the competitiveness of the Port Salaverry-Trujillo during the period 2018-2019, for which a population and sample of study has been considered consisting of six customs, port or maritime agencies located in the district of Salaverry-Trujillo; for the collection of results the technique applied to the population under study was used, as well as the interview with the managers or administrators of the areas that the concessionaire has, interview as well as documentary analysis was used, each with its corresponding instrument. From the reached results, it was concluded that the modernization in its infrastructure, positively and significantly influences the competitiveness of the Salaverry-Trujillo Port during the period 2018 - 2019, since it could be evidenced an increased productivity, a higher traffic of ships of greater capacity, reduction of port closures due to maritime anomalies, due to modernization, equipment, constant dredging of the access channel and the maneuvering area, which was maintained an optimal depth, in addition to the implementation of the SHORETENSION hydraulic mooring technology.